Distribusi fungsional verba pada konteks plot dalam wacana narasi dongeng bahasa Indonesia - Poerwadi, Petrus (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2010)
Every type of verb has a specific distribution in the context of plot in the written Indonesian tale narrative discourse (WNDBI). That specific distribution im- plies specific verb functions and meanings in the context of plot in WNDBI. There are three types of verbs dominant in the use of verbs in the WNDBI, namely materi- al-process verbs, relational-process verbs, and mental-process verbs. Types of claus- es, internal pattern of clauses embedded by certain types of verbs, and characteristics of participants have effects on the functions and meanings of the clauses in WNDBI. The written Indonesian tale narrative discourse possesses a characteristic of accentu- ating physical conflicts among the participants. This is marked by the intensive use of material-process verbs in the stage of conflictI.